2017
DOI: 10.3354/meps12304
|View full text |Cite
|
Sign up to set email alerts
|

Trophic overlap in mobulid rays: insights from stable isotope analysis

Abstract: Mobulid rays, a group of closely related filter-feeders, are threatened globally by bycatch and targeted fisheries. Their habitat use and feeding ecology are not well studied, and most efforts have focused on temporally limited stomach content analysis or inferences from tagging data. Previous studies demonstrate a variety of different diving behaviors across species, which researchers have interpreted as evidence of disparate foraging strategies. However, few studies have examined feeding habitats and diets o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 86 publications
2
65
0
Order By: Relevance
“…The main driver of whale shark occurrence at Donsol appears to be prey related as sightings coincide with periods of higher productivity in the region (Gordon et al, 2011;Stewart et al, 2017). Diatom blooms appear to dominate the plankton composition in Donsol between January and August.…”
Section: Discussionmentioning
confidence: 99%
“…The main driver of whale shark occurrence at Donsol appears to be prey related as sightings coincide with periods of higher productivity in the region (Gordon et al, 2011;Stewart et al, 2017). Diatom blooms appear to dominate the plankton composition in Donsol between January and August.…”
Section: Discussionmentioning
confidence: 99%
“…Planktivorous elasmobranchs tend to follow productive ephemeral pulses that may vary in time and space (Sims, 2003;Rohner et al, 2013). The presence of higher numbers of pregnant females in the region could be related to the high primary productivity and food availability in the area for these species Stewart et al, 2017). Investigations based on catch data coupled with GPS tracks of fishing vessels and environmental parameters (i.e., primary productivity) would provide further insight on areas with higher densities of pregnant females and this relationship with food availability.…”
Section: Speciesmentioning
confidence: 99%
“…A monitoring program of this fishery revealed that over 2,000 individuals were landed per season (Authors, unpub data). The fishing season for mobulids coincided with the northeast monsoon when increased upwelling leads to higher primary productivity in surface waters (Cabrera et al, 2011;Gordon et al, 2011), with prolific pulses of krill Euphausia diomedeae on which mobulids feed in the area Stewart et al, 2017). The four species studied here were caught with drift nets, a targeted but not selective fishing gear, resulting in the catch of M. birostris despite it being protected nationally since 1998 (Fisheries Administrative Order 193; Republic of the Philippines., 1998), and other elasmobranchs, such as thresher shark Alopias spp., juvenile silky sharks Carcharhinus falciformis, and large bony fishes such as billfishes.…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have described the diet of sympatric Mobula rays. Dietary analysis of Mobula species has been conducted using microscopy of stomach contents (Notarbartolo‐Di‐Sciara, ; Rohner et al, ), as well as stable isotope analyses (Sampson, Galvan‐Magana, Silva‐Davila, & Aguiniga‐Garcia, ; Stewart et al, ). Microscopy provides detailed information on taxa consumed for a particular individual at a specific period of time (Hyslop, ), while stable isotope analysis provides insights into relative trophic level and the sources of carbon supporting diets, that are integrated over time (Peterson & Fry, ).…”
Section: Introductionmentioning
confidence: 99%
“…Few fish species have been identified as prey items, with the exception of M. birostris stomachs containing myctophids (small, mesopelagic fishes) and M. tarapacana containing Sardinella and Cubiceps spp. in the Philippines (Rohner et al, ; Stewart et al, ). One individual M. tarapacana was reported to have 27 fish in its stomach (from the Gulf of California), which were thought to be carangids (family of fish containing jacks, jack mackerels, runners, and scads), or smaller anchovy‐like species (Notarbartolo‐Di‐Sciara, ).…”
Section: Introductionmentioning
confidence: 99%